2015
DOI: 10.1371/journal.pone.0122590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Asymmetric Nuclear Introgression, Introgressive Mitochondrial Sweep, and Purifying Selection on Phylogenetic Reconstruction and Divergence Estimates in the Pacific Clade of Locustella Warblers

Abstract: When isolated but reproductively compatible populations expand geographically and meet, simulations predict asymmetric introgression of neutral loci from a local to invading taxon. Genetic introgression may affect phylogenetic reconstruction by obscuring topology and divergence estimates. We combined phylogenetic analysis of sequences from one mtDNA and 12 nuDNA loci with analysis of gene flow among 5 species of Pacific Locustella warblers to test for presence of genetic introgression and its effects on tree t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
4
18
0
2
Order By: Relevance
“…However, our goal here is to provide a retrospective analysis on the mtDNA era of phylogeography and estimate the credibility of nearly three decades of mtDNA studies. Many studies have found that the results based on multiple nuclear genes or genome-wide data are often consistent with those based on one single mtDNA gene data in phylogeographic patterns or species delimitation ( [8,11,[44][45][46]56]; but see [5,41,42]). Here, we provide empirical data confirming the assertion that mtDNA is a useful marker for detecting recent population differentiation because of its fast coalescent time at least in avian taxa (figure 3).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, our goal here is to provide a retrospective analysis on the mtDNA era of phylogeography and estimate the credibility of nearly three decades of mtDNA studies. Many studies have found that the results based on multiple nuclear genes or genome-wide data are often consistent with those based on one single mtDNA gene data in phylogeographic patterns or species delimitation ( [8,11,[44][45][46]56]; but see [5,41,42]). Here, we provide empirical data confirming the assertion that mtDNA is a useful marker for detecting recent population differentiation because of its fast coalescent time at least in avian taxa (figure 3).…”
Section: Resultsmentioning
confidence: 81%
“…The high mutation rate, fast coalescence time owing to a small effective size and matrilineal inheritance make mtDNA more likely to track lineage divergence than any single nuclear gene, and is thus a relatively leading molecular indicator of population differentiation [2]. Nevertheless, analyses of mtDNA generate a single-gene tree and any single-locus tree could present a biased view of species history owing to the stochastic nature of the coalescence process or effects of selection [3][4][5]. In effect, the inferences from the first three decades of mtDNA phylogeography have been called into question [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Однако следует отдавать себе отчет в том, что сравнение последовательностей разных генов может приводить к различным результатам (Roos et al, 2011;Oliver, 2013). Чем моложе сравниваемые виды, тем выше риск появления резко различающихся оценок возраста одних и тех же видов, главным образом, из-за неполного расхождения предковых линий и митохондри-альной либо ядерной трансгрессии (Bossu, Near, 2009;Roos et al, 2011;Oliver, 2013;Drovetski et al, 2015).…”
unclassified
“…Такие несоответствия объяснимы митохондриальными и ядерными интрогрес-сиями, и, как правило, их связывают со временными на-рушениями репродуктивного барьера в обстоятельствах, когда один из видов гораздо более многочисленнее, чем другой (Bossu, Near, 2009;Thompson et al, 2010;Nevado et al, 2011;Roos et al, 2011;Drovetski et al, 2015).…”
unclassified